Ueno's brown frog Rana uenoi indiscriminately ceases calling in the presence of daytime birds. Issue 3 (3rd May 2020) - Kim, Kyungmin; Macias, Daniel; Borzée, Amaël; Jang, Yikweon
Abstract : Animals need to recognise predators to assess threats and adjust their behaviour accordingly. Acoustic cues produced to attract mates may also be intercepted by predators, and signallers can use both visual and acoustic cues to detect predators and initiate escape or defensive behaviours. Here, to test whether Ueno's brown frogs ( Rana uenoi ) advertising during daytime are able to visually and aurally recognize predatory birds, we monitored calling activity at 27 active breeding sites where birds were also known to occur. Based on visual and aural observations, frogs were significantly less likely to be calling when birds were present than when absent. However, we failed to determine whether male R. uenoi distinguished among predator and non-predator species, responding to the presence of all bird species with cessation of calling. While daytime calling activity decreased in the presence of birds, the maximum egg clutch count per site used as a proxy for reproductive output was unaffected by daytime presence of birds. Our results suggest that R. uenoi uses visual cues to detect disturbances, but that its ability to visually assess the risks posed by individual species is minimal.